LEDAKAN AMONIUM NITRAT: FAKTOR PEMICU URGENSI PERUBAHAN SISTEM POLITIK DI LEBANON - Harmiyati, Harmiyati (Jurnal Paradigma, 2021)
Lebanon, a country with a confessional political system, fragmented its political power based on the composition of religions. The political system is fragile and become an obstacle in creating national integrity. The fragility of the political system has always been the source of unstable politics and economics, however, the system remains until now. These problems are worsened by the fact that Lebanese community are exclusive in certain areas based on their religion, thus it triggers the imbalance of social and economic. On the other hand, the number of corruptions in the country has increased among the political elites hence social, political, and economical chaos are undeniable.